Anatomical Rationale for the Choice of Surgical Intervention for an Ingrown Nail - Sh. A. Makhmudov; E. M. Fominykh; V. F. Zubritsky; A. A. Kanibolotsky; P. D. Varfolomeyeva; G. A. Platonova; O. S. Rogovaya (Неотложная медицинская помощь)
BACKGROUND. An ingrown toenail is one of the reasons for surgical intervention: it accounts for up to 20 % of all operations in clinics. At the same time, conservative and surgical approaches to treatment are not reliable enough: up to 70% of cases are complicated by relapses.   AIM OF STUDY. To study the topographic location and ratio of cells in the growth zone of the nail plate, necessary for planning the volume of intervention in the treatment of ingrown toenails.   MATERIAL AND METHODS. The material for conducting our own research was samples of the cadaver nail complex, without identified pathologies, from 20 objects of different ages and genders. Studies were carried out using histological, immunofluorescent and microscopic methods.   The results were compared with available literature data, clarifying the most important structural features. The data obtained will make it possible to reasonably plan the volume of intervention during operations for ingrown nails, as well as to reduce the number of unsatisfactory results of operations on the nail complex in case of injury and nail diseases.